Impact of corporate governance on firm’s performance The case of the Portuguese Listed Firms - Lisboa, Inês (2021)
Purpose: Corporate governance issues have been particular important in the last years because of diverse international scandals (e.g. Enron e a WorldCom in the US, Parmalt in Italy, and Banco Português de Negócios in Portugal, among others). This calls for the need for a reformulation of governance mechanisms to minimize agency conflicts and restore confidence in capital markets as well as transparency of the company's economic and financial situation. The choice of some corporate governance issues may have impact in the company’s performance, as it may influence agency costs between the principal and managers and between type of investors and may impact the firm’s financial decision. In this sense, this paper aims to analyze the impact of corporate governance’ characteristics on the financial performance of Portuguese listed firms. Design/methodology/approach: A panel data of listed companies on Euronext Lisbon, between 2012 and 2016, and the multiple linear regression model, was used. Findings: We find that results depend on the performance ratio used. The main results suggest that the size and independence of the board of directors have impact on the company’s performance. Moreover, we find that financial investors give relevance to best corporate governance practices. Originality: Most studies analyzing this thematic focus on major countries. This work focuses on a small-size country, where corporate governance mechanisms were questioned due to diverse bankruptcies and financial scandals. Moreover, accounting and market-based performance are addressed to see the main differences and similarities.